Parental imprisonment as a risk factor for cardiovascular and metabolic disease in adolescent and adult offspring: A prospective Australian birth cohort study - Michael E. Roettger; Brian Houle; Jake Najman; Tara R. McGee (Elsevier, 2022)
Objectives: Parental imprisonment is linked with child health in later life. The present study provides the first prospective cohort analysis and non-U.S. based study examining parental imprisonment and cardiometabolic risk factors in adolescence and adulthood. Methods: The study followed 7,223 children born from live, singleton births from 1981 to 1984 in Brisbane, Australia. Data on parental imprisonment was collected at mother interview when the children were ages 5 and 14. Our sample analyzes offspring with biometric data collected by health professionals, including 3,794 at age 14, 2,136 at age 21, and 1,712 at age 30. Analyses used multivariate linear and logistic regression, and time-varying growth curve models. Results: Among female respondents, parental imprisonment at ages ≤5 was associated with higher body-mass index (BMI) at ages 14, 21, and 30; higher systolic blood pressure (SBP) and diastolic blood pressure (DBP) at age 30; and increased sedentary hours, larger waist circumference, and odds of a high-risk waist circumference at age 30. Parental imprisonment when the child was aged ≤14 was associated with increased BMI and SBP at age 30 for females. In growth-curve models, parental imprisonment when the child was aged ≤5 and ≤ 14 among females was linked with increased BMI; parental imprisonment when the child was aged ≤5 was associated with increased SBP and DBP. No significant associations were observed for males. Conclusions: Using prospective cohort data, our results support research showing that parental imprisonment, particularly in early childhood, is associated with increased BMI, blood pressure, sedentary hours, and waist circumference in females in early adulthood. These findings implicate parental imprisonment as a risk factor for cardiometabolic health issues in later life among females.